Reality of Application of Knowledge Management at Public schools of Qabatiya and Salfit Districts, Palestine from the Point of View of their Principals - Basem Mohammad Shalash; Nedal Fayez Abd Elghafour (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the reality of application of knowledge management at public schools of Qabatiya and Salfit districts, Palestine, from the point of view of their principals, and whether there are statistically significant differences in the principals' responses due to  gender, years of experience and academic qualifications. The study followed a descriptive analytical approach. It was applied to a sample of (91) principals through a questionnaire that consisted of three areas (school administration, teachers, and capabilities and techniques). The results showed that the principals' responses came at the level of the tool and at the level of the areas of school administration and teachers, and came at the level of the field of capabilities and techniques to a very large extent. The results did not show that there were statistically significant differences at the level of the school administration, capabilities or techniques due to gender or years of experience. Moreover, there were no differences due to educational qualification at the level of the tool as a whole and at the level of teachers' capabilities and techniques. The results also revealed that there are differences at the level of teachers' specialization and at the level of the tool as a whole due to gender in favor of female principals and due to the variable of years of experience in favor of principals whose experience is less than five years. In addition, there are differences due to educational qualification in favor of principals who hold a master's degree or higher.